Identification of Infant Crying Using Mel-Frequency Cepstral Coefficient (MFCC) and Artificial Neural Network (ANN) Methods - Azhari, Ahmad; Destiyanti, Intan (Association for Scientific Computing Electrical and Engineering (ASCEE), 2022)
The crying of infants aged 0-3 months can be classified according to their needs, as identified by Dunstan Baby Language, which consists of specific sounds denoting different needs. These sounds include